2020
DOI: 10.1126/sciadv.abc0221
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear DICER–circular RNA complex drives the deregulation of the glioblastoma cell microRNAome

Abstract: The assortment of cellular microRNAs (“microRNAome”) is a vital readout of cellular homeostasis, but the mechanisms that regulate the microRNAome are poorly understood. The microRNAome of glioblastoma is substantially down-regulated in comparison to the normal brain. Here, we find malfunction of the posttranscriptional maturation of the glioblastoma microRNAome and link it to aberrant nuclear localization of DICER, the major enzymatic complex responsible for microRNA maturation. Analysis of DICER’s nuclear int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…Mature miRNAs are thought to operate mostly in the cytosolic compartment; however, in specific conditions some of them could be found in the nucleus (Hwang, Wentzel et al, 2007, Liu, Lei et al, 2018, Politz, Hogan et al, 2009. In agreement with this, in glioma cells, the major enzymatic complex responsible for the final step of miRNA processing, Dicer, is aberrantly localized to the nucleus (Bronisz et al, 2020). To investigate miR-10b subcellular localization, we fractionated glioma cells into cytosolic and nuclear fractions.…”
Section: Mir-10b Binds To Snrna U6 In Glioma Cellsmentioning
confidence: 66%
See 1 more Smart Citation
“…Mature miRNAs are thought to operate mostly in the cytosolic compartment; however, in specific conditions some of them could be found in the nucleus (Hwang, Wentzel et al, 2007, Liu, Lei et al, 2018, Politz, Hogan et al, 2009. In agreement with this, in glioma cells, the major enzymatic complex responsible for the final step of miRNA processing, Dicer, is aberrantly localized to the nucleus (Bronisz et al, 2020). To investigate miR-10b subcellular localization, we fractionated glioma cells into cytosolic and nuclear fractions.…”
Section: Mir-10b Binds To Snrna U6 In Glioma Cellsmentioning
confidence: 66%
“…However, miR-10b does not contain such nuclear localization motifs. At least two pieces of evidence provide support for the nuclear miR-10b maturation scenario: first, the finding of Ago2 and, more recently, of Dicer in the nucleus of specific cells, including glioma (Bronisz et al, 2020, Burger, Schlackow et al, 2017, Castanotto, Zhang et al, 2018, Chu, Yokota et al, 2021, Gagnon, Li et al, 2014, Liu et al, 2018, and second, the co-IP of the spliceosomal SART3 and PRPF8 complexes with Ago2, the core endonucleolytic components of RISC that efficiently pools-down the entire miR-10b population from glioma cells. There is also emerging evidence that RISC components continuously shuttle between the nucleus and cytoplasm (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To explore the relevance of circRNA and GBM progression, we analyzed an online‐available dataset (GSE146463 37 ). The results revealed that several circRNAs were differentially expressed between GBM tissues and NC (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that compared with the normal brain, a variety of tumor-suppressive miRNAs of glioblastoma is signi cantly down-regulated. However, the mechanism is still not clear (19). In the present study, we sequenced the CSF exosomes and matched tumor tissue samples from 59 patients.…”
Section: Introductionmentioning
confidence: 90%